A Stage-Structured Model with Two Time-Steps for Analyzing the Population Dynamics of Rhea Americana - Simoy, Maria Veronica (2008)
The Ñandú or Rhea americana is an autochthonous species perfectly adapted to the pampas environment and only distributed in South America. The species exhibits an unusual breeding system combining polygyny, polyandry, communal nests and exclusive male parental care, which seems to contradict the idea of selfish genes. Our aim has been to construct a mathematical model based on the short term population dynamics of Rhea, living in the wild or in semi-captivity, and taking into account environmental factors that vary from year to year. Due to the characteristics of its life cycle, it was necessary to develop a model that allows us to differentiate between the survival and fertility rates of each age group and the distinct behavior during breeding and non-breeding seasons. Therefore, a quarterly differentiated stage-structured discrete model was needed. Time steps of different lengths are used for modeling chicks or ?charos? on the one hand, and juveniles and adults on the other. Environmental variables have been incorporated into the model because they affect the reproductive success of the species. Different scenarios are given as illustrations of the model use. Finally, the possibility of harvesting has been introduced in the model. The model is intended as a first step towards more refined models and systematic data gathering with the purpose of leading the way to a computational tool for risk assessment and decision-making.